Orca rescue! : the true story of an orphaned orca named Springer - Sandstrom, Donna (Kids Can Press, 2021)
"In 2002, a young orca was discovered in Puget Sound near Seattle, Washington -- lost, starving, alone and 300 miles away from her home waters in Canada. Six months later, the orca, named Springer, was rescued, rehabilitated and reunited with her pod near the north end of Vancouver Island. It was the first successful orca rescue and reunion in history! Now, Springer's complete story is told in a kid-friendly narrative, accompanied by evocative watercolour illustrations and interspersed with short non-fiction spreads that offer more information about orcas and the intelligent and playful behavior that has made them a favorite animal of kids everywhere. Readers will discover what it's like on the frontlines of whale rescue, how we can help endangered species, and the power of working together to achieve a common goal. Written by a volunteer in the rescue effort, Orca Rescue shares new behind-the-scenes details and stories about this incredible effort to send a little whale home."--